Opioid-Free Thyroid and Parathyroid Operations: Are Patients Satisfied With Pain Control?. Issue 4 (April 2023) - Leader, Preston W.; Oyler, Douglas R; Carter, Tonya M; Damron, Donna S.; Lee, Cortney Y.; Sloan, David A; Inabnet, William B; Randle, Reese W.
Background: The aim of this study was to evaluate pain control and patient satisfaction using an opioid-free analgesic regimen following thyroid and parathyroid operations. Methods: Surveys were distributed to all postoperative patients following total thyroidectomy, thyroid lobectomy, and parathyroidectomy between January and April 2020. After surgery, patients were discharged without opioids except in rare cases based on patient needs and surgeon judgment. We measured patient-reported Numeric Rating Scale (NRS) pain scores and satisfaction categorically as either satisfied or dissatisfied. Results: We received 90 of 198 surveys distributed, for a 45.5% response rate. After excluding neck dissections (n = 6) and preoperative opioid use (n = 4), the final cohort included 80 patients after total thyroidectomy (26.3%), thyroid lobectomy (41.3%), and parathyroidectomy (32.5%).The majority reported satisfaction with pain control (87.5%) and the entire surgical experience (95%). A similar proportion of patients reported satisfaction with pain control after total thyroidectomy (90.9%), thyroid lobectomy (90.5%), and parathyroidectomy (80.8%), indicating the procedure did not significantly impact satisfaction with pain control ( P = .47). Patients who reported dissatisfaction with pain control were more likely to receive opioid prescriptions (30% vs 2.9%, P < .01), but the majority still reported satisfaction with their entire operative experience (70%). Discussion: Even with an opioid-free postoperative pain regimen, most patients report satisfaction with pain control after thyroid and parathyroid operations, and those who were dissatisfied with their pain control generally reported satisfaction with their overall surgical experience. Therefore, an opioid-free postoperative pain control regimen is well tolerated and unlikely to decrease overall patient satisfaction.